2003
DOI: 10.1007/s00535-002-1147-7
|View full text |Cite
|
Sign up to set email alerts
|

Adenosquamous carcinoma of the jejunum

Abstract: Primary adenosquamous carcinomas of the intestine are rare, particularly in the small intestine. One case, in the jejunum of an adult female, is described here. The patient was a 70-year-old Japanese woman presenting with upper abdominal pain. Computed tomography of the abdomen showed a mass in the small intestine, measuring 86 x 44 mm, and a double-contrast barium study revealed a filling defect in the upper jejunum. The patient was diagnosed as suffering from upper small-intestinal cancer, and surgical excis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…However, in the jejunum and ileum, it is a curiosity. Only six cases have been documented in the English‐language medical literature 1–6 . A review of our archives found that the present case was the first in 50 years.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…However, in the jejunum and ileum, it is a curiosity. Only six cases have been documented in the English‐language medical literature 1–6 . A review of our archives found that the present case was the first in 50 years.…”
Section: Discussionmentioning
confidence: 81%
“…Adenosquamous carcinomas have been described in various organs, but are extremely rare in the small intestine. To date, only three jejunal and three ileal cases have been reported in the English‐langulage medical literature 1–6 . We present here a case of jejunal adenosquamous carcinoma in an 80‐year‐old woman, with a predominant squamous component throughout the tumor, and mesenteric metastasis from the adenocarcinoma element, and with foci of morphological transition from the glandular component to the squamous component.…”
mentioning
confidence: 94%
“…In areas where glandular and squamous epithelia are normally juxtaposed, such as the esophago-gastric or the rectal-anal junction, it is considered that both adenocarcinoma and squamous carcinoma could occur independently and collide by chance. This scenario, however, does not seem to be applicable to the case described by Wada et al, 1 …”
mentioning
confidence: 51%
“…According to this concept, cancer behavior, including the determination of phenotype, is dependent on the noncancerous cells surrounding the cancer tissue. Therefore, in the case reported by Wada et al, 1 it can be considered that there might have been some alterations defining adenocarcinoma in the surrounding normal tissue, and subsequently the different phenotype, i.e., the squamous feature, appeared. All four of the above theories provide only speculative answers in this case, and we cannot resolve this question yet.…”
Section: In Terms Of Normal Intestinalmentioning
confidence: 94%
See 1 more Smart Citation